SmbHLH37 Functions Antagonistically With SmMYC2 in Regulating Jasmonate-Mediated Biosynthesis of Phenolic Acids in Salvia miltiorrhiza - Du, Tangzhi; Niu, Junfeng; Su, Jiao; Li, Shasha; Guo, Xiaorong; Li, Lin; Cao, Xiaoyan; Kang, Jiefang (Frontiers in Plant Science, 2018)
Jasmonates (JAs) are integral to various defense responses and induce biosynthesis of many secondary metabolites. MYC2, a basic helix-loop-helix (bHLH) transcription factor (TF), acts as a transcriptional activator of JA signaling. MYC2 is repressed by the JASMONATE ZIM-domain (JAZ) proteins in the absence of JA, but de-repressed by the protein complex SCFCOI1 on perception of JA. We previously reported that overexpression of SmMYC2 promotes the production of salvianolic acid B (Sal B) in Salvia miltiorrhiza. However, the responsible molecular mechanism is unclear. Here, we showed that SmMYC2 binds to and activates the promoters of its target genes SmTAT1, SmPAL1, and SmCYP98A14 to activate Sal B accumulations. SmbHLH37, a novel bHLH gene significantly up-regulated by constitutive expression of SmMYC2, was isolated from S. miltiorrhiza for detailed functional characterization. SmbHLH37 forms a homodimer and interacts with SmJAZ3/8. Overexpression of SmbHLH37 substantially decreased yields of Sal B. SmbHLH37 binds to the promoters of its target genes SmTAT1 and SmPAL1 and blocks their expression to suppress the pathway for Sal B biosynthesis. These results indicate that SmbHLH37 negatively regulates JA signaling and functions antagonistically with SmMYC2 in regulating Sal B biosynthesis in S. miltiorrhiza.